Hubungan Kadar Hemoglobin Ibu Hamil Trimester 3 dengan Antropometri Padang dan Skor APGAR di RSUP. DR. M. Djamil Padang - Muhammad Alhardi Nurdin; Yusrawati Yusrawati; Elmatris Elmatris (Jurnal Ilmu Kesehatan Indonesia, 2021)
Hemoglobin is one of the most important parts of blood in pregnant women because hemoglobin supplies oxygen and nutrients throughout the body, including the fetus a mother is carrying. If the hemoglobin level is outside of the normal range, newborn babies will have abnormal anthropometric features and APGAR scores. This study aims to determine whether there is a relationship between hemoglobin in pregnant women with anthropometry and APGAR score of newborns. This study uses a retrospective analytics method and is supported by statistical analysis using the Pearson correlation test to obtain the relationship of independent variables with dependent variables. From 100 patient data taken, we found a significant relationship with a weak correlation for the relationship of hemoglobin of pregnant women with infant weight, a significant relationship with a weak correlation for the relationship of hemoglobin of pregnant women with body length, a significant relationship with a weak correlation for the relationship of pregnant women with the circumference of a baby's head, a significant association with a weak correlation for the relationship of hemoglobin in pregnant women with an APGAR score of 5 ', and a meaningful relationship with a weak correlation for an association of hemoglobin in a pregnant woman with an APGAR score of 10'. So, it can be concluded that there is a significant relationship between hemoglobin in third trimester pregnant women with anthropometry and APGAR score of newborns. Keywords: anthropometry, APGAR score, hemoglobin